ナンキョク ショウワキチ ダイ10 キョジュウトウ ノ フクゲン クミタテ ト タイキュウセイ ノ モクシ チョウサ - 半貫, 敏夫; ハンヌキ, トシオ; 岸, 明; キシ, アキラ; 平山, 善吉; ヒラヤマ, ゼンキチ; 佐野, 雅史; サノ, マサシ; Hannuki, Toshio; Kishi, Akira; Hirayama, Zenkichi; Sano, Masashi (2002)
P(論文) 昭和基地で約29年間、居住施設として使われてきた木質プレハブ建築システムを日本に持ち帰り、その耐久性を調査した。先ず、持ち帰った部品を用いて基礎を除く鉄骨架台から上の建物部分を組み立てて復元し、建物全体の劣化状況を観察した。復元工事は5日間、延べ22人の労働力によって完成した。工事は建築専門職人によって行われたが、短期間の人力作業という条件で設計された建築システムの優れた性能が証明された。それぞれの部品はまだ数回の組み立て、解体に耐えられる性能を維持していると判断された。 復元建物の耐久性目視調査の結果、部分的に補修を要する個所もあったが、建物全体としては、まだ設計条件をクリアする性能を維持していることが分かった。パネル外装のめっき鋼板は防火が目的であったが、木質パネルの保護層として有効に作用し、合板の劣化を遅らせた。防水設計を改良すればさらに建物全体の耐久性を増すことが可能である。 The living hut was built by the 10th Japanese Antarctic Research Expedition (JARE-10) at Syowa Station in 1969. The living hut, which had been used over 29 years at Syowa Station, was demolished and the prefabricated building elements of the hut were brought back to Japan in 1998. The building elements were reconstructed for the durability test and the present conditions of the reconstructed living hut were investigated. The reconstruction work of the hut was finished within 5 days and with a total of 22 workers. The elements and devices were usable on the whole. The building can be reused if damaged parts are restored and external facing and interior finish are renewed. departmental bulletin paper